A hypothesis to explain how the sensory cortices respond in the appropriate sensory mode - Hocker, Geoffrey A (The Royal Society of Medicine, 2003)
How does an area of sensory cortex recognize the specific nature of the sensory mode of the stimulus that arrives from the peripheral sensory receptor, when nerve impulses are only all-or-nothing action potentials? Work in animals has shown that an area of sensory cortex can learn in which mode to respond. A period of cortical learning is required for phantom limb phenomena to develop, and for the ocular blind to dream in the visual mode. Arguing from these facts I develop the hypothesis that within the sensory cortices there are neurons that learn by neurotropic factor transport from their sensory receptors to function as surrogates for those receptors, thus enabling sensory cortical response to be modally specific.